Priority indicators of sports activity of jumps in water at the stage of advanced sports training - Romanchuk, S.; Oderov, A.; Klymovych, V.; Arabskyi, A.; Lesko, O.; Fedak, S.; Dunets-Lesko, A.; Bobko, Y.; Olkhovy, O.; Liudovyk, T. (SportMont, 2020)
An analysis of the sports activities of divers conducted over three years, with boys (n=104) and girls (n=102), has determined that the sports activities of such divers are in general similar. For instance, indicators of physical development and sports-technical preparedness are similar in significance and contribution to the factorial structure for boys (11.4-21.8%) and girls (12.8-22.6%). The indicators of nystagmus reactions to rotational loads in 10-year-olds are common for all groups (boys: 10.0%; girls: 6.9%) but differ in their place in the factorial structure and contribution to the total dispersion. Thus, in the boys` group, indicators of physical development and sports-technical preparedness remain valid throughout the study period, while girls aged 12 to 13 experience changes in the significance of the identified factors and the integration of factors` indicators, which makes their interpretation difficult. The analysis carried out will allow the development of an integrated assessment of athletic suitability, taking into account the rank correlation of the indicators of children`s sports-technical preparedness by years of training.